Small kernel2 Encodes a Glutaminase in Vitamin B6 Biosynthesis Essential for Maize Seed Development. Issue 2 (13th April 2017) - Yang, Yan-Zhuo; Ding, Shuo; Wang, Yong; Li, Cui-Ling; Shen, Yun; Meeley, Robert; McCarty, Donald R.; Tan, Bao-Cai
Abstract : A small kernel mutant in maize highlights vitamin B6 biosynthesis in embryogenesis and endosperm development. Abstract: Vitamin B6, an essential cofactor for a range of biochemical reactions and a potent antioxidant, plays important roles in plant growth, development, and stress tolerance. Vitamin B6 deficiency causes embryo lethality in Arabidopsis ( Arabidopsis thaliana ), but the specific role of vitamin B6 biosynthesis in endosperm development has not been fully addressed, especially in monocot crops, where endosperm constitutes the major portion of the grain. Through molecular characterization of a small kernel2 ( smk2 ) mutant in maize, we reveal that vitamin B6 has differential effects on embryogenesis and endosperm development in maize. The B6 vitamer pyridoxal 5′-phosphate (PLP) is drastically reduced in both the smk2 embryo and the endosperm. However, whereas embryogenesis of the smk2 mutant is arrested at the transition stage, endosperm formation is nearly normal. Cloning reveals that Smk2 encodes the glutaminase subunit of the PLP synthase complex involved in vitamin B6 biosynthesis de novo. Smk2 partially complements the Arabidopsis vitamin B6 -deficient mutant pdx2.1 and Saccharomyces cerevisiae pyridoxine auxotrophic mutant MML21. Smk2 is constitutively expressed in the maize plant, including developing embryos. Analysis of B6 vitamers indicates that the endosperm accumulates a large amount of pyridoxamine 5′-phosphate (PMP). These results indicate that vitamin B6 is essential to embryogenesis but has a reduced role in endosperm development in maize. The vitamin B6 required for seed development is synthesized in the seed, and the endosperm accumulates PMP probably as a storage form of vitamin B6 .